AGRONOMIYA TARAWÍNDAǴÍ SÚWRETLERDE KONTRASTTÍ ASÍRÍW USÍLLARÍ - Mamatov, N.S.; Niyozmatova, N.A.; Jalelova, M.M.; Samijonov, A.N.; Tojiboeva, Sh.X. (SCIENCE and SOCIETY, 2023)
Uunmanned aerial vehicle imagery has become an important tool in the field of agronomy. Such images are used to identify areas of plant damage and potential loss of productivity. However, because the images are often low contrast, it poses a problem in properly analyzing the data. Therefore, image contrast enhancement is very important to improve quality and reliability. In this research work, the evaluation of several methods of contrast enhancement in low-contrast images with dimensions that determine image quality is considered.